Eksplorasi Penggunaan Pendekatan Konstruktivis dalam Proses Perkuliahan - Yendrita Yendrita; Sri Nengsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to explore the use of a constructivist approach in the lecture process in the Biology Education study program, STKIP Yayasan Abdi Pendidikan Payakumbuh. The method used is the descriptive method. The instrument of this research is a set of questionnaires distributed to all students of the Biology Education study program at the Abdi Pendidikan Payakumbuh Foundation who are registered in the even semester of the 2019/2020 academic year. The results showed that the use of a constructivist approach in general in lectures at the Biology Education Study Program of the Abdi Pendidikan Foundation was carried out by 76.25%, the process of forming concepts based on constructivists was 77.08%, the use of constructivist learning principles was 75.27%, the use of unique characteristics constructivist by 74.72% and the implementation of learning with a constructivist approach of 78.03%. In conclusion, the constructivist approach has been used well in the lecture process at the Biology Education Study Program STKIP Yayasan Abdi Pendidikan Payakumbuh. Keywords: Exploration, Constructivist, Lecture